Endocrinology of flexible development in the flour beetle, Tribolium freemani - Ruang-Rit, Krissana (Kansas State University, 2016)
Insect metamorphosis is driven by two major hormones, juvenile hormone (JH) and ecdysone (Ec). The presence of JH with an Ec peak in each stadium results in larval-larval molting whereas in the last larval instar a decline of JH to undetectable level combined with pulses of Ec leads to larval-pupal metamorphosis. Larval-pupal metamorphosis normally occurs after a certain number of larval instar and upon reaching a certain size (critical weight). However, in the flour beetle, Tribolium freemani, under crowded conditions larva continue larval-larval molting (LLC) without pupation for longer than 14 instars (6 months). Previous studies have implicated high JH titer as preventing the metamorphosis leading to supernumerary molts. My investigation of JH roles in LLC started by asking whether suppression of JH would rescue the LLC phenotype and allow pupal metamorphosis. Using RNA interference (RNAi), I found that under crowded conditions RNAi of T. freemani methyltransferase3 (TfMT3), which encodes a crucial enzyme for the final methylation step in the JH biosynthesis, or RNAi of T. freemani Krüppel homolog1 (TfKr-h1), the JH downstream gene, did not rescue the larvae but resulted in prepupal lethality. Surprisingly, under crowded conditions prepupal lethality was rescued by RNAi of both TfMT3 and TfKr-h1 administered together, although developmental arrest occurred at the pharate adult stage; this is also the phenotype of TfKr-h1 RNAi-treated larvae under isolated conditions. In investigations of the role of Ec titer in LLC, lethality of the larvae with RNAi of TfMT3 under crowded conditions was associated with the loss of the major ecdysteroid peak, while TfKr-h1 RNAi-treated larvae under crowded conditions showed a delayed, but normal, Ec peak occurring at prepupal arrest. The pattern of Ec peak in RNAi of both TfMT3 and TfKr-h1 together was similar to that with TfKr-h1 RNAi alone. I suggest that a hormonal imbalance, high JH and high Ec in the prepupal arrest of TfKr-h1 RNAi, was rescued by RNAi of both TfMT3 and TfKr-h1 for low JH and high Ec. These results demonstrate that the signaling pathways for LLC are through at least two independent pathways; JH biosynthesis and TfKr-h1-mediated JH response.
Keywords: Tribolium freemani; Insect endocrine; Flexible development; JHAMT; Krüppel homolog1; Ecdysone